2020
DOI: 10.1017/laq.2019.96
|View full text |Cite
|
Sign up to set email alerts
|

Food and Society at Real Alto, an Early Formative Community in Southwest Coastal Ecuador

Abstract: We investigated foodways at Real Alto, an early Formative (4400–1800 BC) Valdivia site in coastal Ecuador, using starch and phytoliths recovered from 50 stone tools from three residential and two ceremonial structures, as well as 46 human dental calculus samples, to explore how food reflects the social relationships and economy of the community. Maize was important in daily meals and ceremonial foods by the Middle Valdivia (2800–2400 BC), but it was only one component of an agricultural system that included yu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…3.500 a 2.300 BP (KILLION, 2013;VANDERWARKER;KRUGER, 2012); na cultura Valdivia, do litoral do Equador, entre ca. 6.300 e 3.700 BP (PEARSALL et al, 2020); em Caral, na costa central do Peru, entre ca. 4.000 e 3.600 BP (SHADY SOLÍS, 2014;SHADY SOLÍS et al, 2001); e no litoral sul do Peru de ca.…”
Section: O Contexto Socioeconômico: Cultivo E Produção De Alimentosunclassified
See 1 more Smart Citation
“…3.500 a 2.300 BP (KILLION, 2013;VANDERWARKER;KRUGER, 2012); na cultura Valdivia, do litoral do Equador, entre ca. 6.300 e 3.700 BP (PEARSALL et al, 2020); em Caral, na costa central do Peru, entre ca. 4.000 e 3.600 BP (SHADY SOLÍS, 2014;SHADY SOLÍS et al, 2001); e no litoral sul do Peru de ca.…”
Section: O Contexto Socioeconômico: Cultivo E Produção De Alimentosunclassified
“…Sociedades de meio termo foram extremamente comuns nas Américas, desde milhares de anos atrás até períodos mais recentes (CAROMANO et al, 2013;CHANCA et al, 2021;CORTELETTI et al, 2015;HILBERT et al, 2017;IRIARTE, 2009;IRIARTE et al, 2004;PEARSALL, 2009;PEARSALL et al, 2020;PIPERNO, 2011;PIPERNO;PEARSALL, 1998;WATLING et al, 2018). Um conjunto substancial de dados sugere que a sociedade sambaquiana tenha sido uma delas, tendo adotado uma economia 1 Embora o termo "sambaquieiro" seja dominante na literatura nacional como forma de se referir às pessoas relacionadas aos sambaquis, nossa equipe tem privilegiado o termo "sambaquiano/a".…”
Section: Introductionunclassified
“…First, the settlement contains collective spaces that likely were associated with ceremonial, public activities, alongside domestic spaces that contain little evidence of differentiation. Recent archaeobotanical studies have shown that there was no difference between public, ceremonial, and domestic spaces in the way that agricultural products were processed and consumed (Pearsall et al 2020). This finding points to a sort of democratized ceremoniality where all members had similar access to resources in all spaces of the settlement.…”
mentioning
confidence: 95%
“…On the Pacific coast of South America, the productive Humboldt upwelling system (3°24 ′ S-54°55 ′ S) has sustained coastal adapted populations since the Late Pleistocene. Throughout the Holocene, coastal communities developed mixed economies with distinct degrees of reliance on marine and terrestrialbased resources (Dillehay et al 2022;Knudson et al 2015;Pearsall et al 2020). In southern Chile the intensification of food production during the Late Ceramic period (950-400 cal BP) led to sedentarism and a remarkable demographic upsurge (Campbell and Quiroz 2015).…”
mentioning
confidence: 99%